Analisis Childfree Choice Dalam Perspektif Ulama’ Klasik dan Ulama’ Kontemporer - Adi, Rudi; Afadi, Alfin (Taruna Law: Journal of Law and Syariah, 2023)
Childfree is a term for people who agree to decide not to have children. The term childfree can be defined as a view of a husband and wife who decide not to have children. The decision to choose childfree in household life cannot be separated from the role of husband and wife. The method used in this study is qualitative, with a comparative approach, namely comparing two points of view, namely according to classical and contemporary Islamic scholars. While the type of research used is Library Research, in the sense that all data sources come from written materials related to the topics discussed. The results of the study show that classical scholars do not forbid married couples who agree not to have children (offspring). Because this is confirmed by 'Azl whose law is permitted by Imam Ghazali, contemporary scholars also allow it if husband and wife agree because of certain benefits. So childfree is not included in the prohibited acts, because every married couple has the right to plan and manage household life including having children.